Assessing the Pathogenicity of Fusarium solani on Tomato Seedlings - Zainap Hasan (AlQalam Journal of Medical and Applied Sciences, 2024)
Tomatoes and other vegetables can rot due to post-harvest infections caused by Fusarium species. This study was out to determine Fusarium species that were isolated from tomato plants that were infected, to identify the causative organisms by phenotypic features, and to confirm the pathogenicity of Fusarium solani on tomato plants using pathogenicity tests. The phenotypic of Fusarium isolates was ascertained using potato dextrose agar (PDA) media, with a focus on features such as homogenous cells, growth rates, colony characteristics, macroconidial and microconidial shapes and sizes, and chlamydospores. Fifteen Fusarium isolates in all were acquired. Four isolates were identified as Fusarium solani then tested for pathogenicity. All tested Fusarium isolates were pathogenic to tomato plants with different levels of severity. Uninoculated controls did not exhibit any symptoms of root rot. F19 isolate was the most pathogenic with a DSI of 47.5%, while the least were F7, F22 and F11 isolates with a DSI of 42.5%, 37.5%, 35% respectively. The potential mycotoxin production of these pathogenic isolates in tomato plants can cause health problems when consumed. تعد أنواع الفيوزاريوم أحد مسببات الأمراض الشائعة لأمراض ما بعد الحصاد التي تسبب تعفن الطماطم والخضروات الاخرى . كانت أهداف هذه الدراسة هي تحديد تنوع عزلات الفيوزاريومالمعزوله من نباتات الطماطم المصابة، وتحديد العزلات المسببه لمرض تعفن الجذر باستخدام الخصائص المظهرية. تم استخدام أوساط اجار دكستروز البطاطس لتحديد المستعمرة، ومعدلات النمو، والخلايا المتجانسة والجراثيم الكلاميديا. تم الحصول على اجمالي 15 عزله من الفيوزاريوم. تم تشخيص اربع عزلات منها على انها فيوزاريوم سولاني ثم تم اختبار قدرتها الامراضية باستخدام اختبار الامراضية. فكانت جميع عزلات الفيوزاريوم المختبرة مسببه للأمراض لنباتات الطماطم بمستويات مختلفة من الشدة. ولم تظهر الضوابط غير الملقحة اي أعراض لعفن الجذور، حيث كانت عزلة F19 هي الأكثر خطوره حيث بلغ مؤشر DSI 47% ، بينما كانت العزلات الأقلF7، F22،F11 بمؤشر DSI 42.5%، 37.5%، 35% على التوالي. حيث يمكن ان يسبب انتاج السموم الفطرية المحتملة لهذه العزلات مشاكلا صحية عند استهلاكها